Nanomaterials and the human lung: what is known and what must be deciphered to realise their potential advantages? (Swiss Medical Weekly, 2013)
Due to the constant expansion within the nanotechnology industry in the last decade, nanomaterials are omnipresent in society today. Nanotechnology-based products have numerous different applications ranging from electronic (e.g., advanced memory chips) to industrial (e.g., coatings or composites) to biomedical (e.g., drug delivery systems, diagnostics). Although these new nanomaterials can be found in many “everyday” products, their effects on the human body have still to be investigated in order to identify not only their risk, but also their potential benefits towards human health. Since the lung is commonly thought to be the main portal of entry into the human body for nanomaterials released within the environment, this review will attempt to summarise the current knowledge and understanding of how nanomaterials interact with the respiratory tract. Furthermore, the advantages and disadvantages of different experimental model systems that are commonly used to study this exposure route to the human body will be discussed.